2023
DOI: 10.3390/rs15030729
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and Location of Drainage Divides Affected by Tilting Uplift in Sado Island, Japan

Abstract: Drainage divide is a dynamic feature that migrates in response to tectonic activity. The asymmetric uplift between two adjacent basins causes the divide migration from a slower to faster uplift area. Sado Island, Japan, has been affected by southeastward tilting uplift for ca. 300k years. Despite the faster uplift on the northwest, the main divides have existed on the southeast side of the geometric center of the island, with no other feature suggesting tectonic inversion of the tilting direction. In this stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…300k years. Sakashita and Endo [25] conducted a digital-elevation-modelbased investigation that focused on divide migration. They concluded that the main divides of Sado have presumably continued to slowly migrate toward the area of faster uplift.…”
Section: Worldwide Tectonic Geomorphological Research Using High-reso...mentioning
confidence: 99%
“…300k years. Sakashita and Endo [25] conducted a digital-elevation-modelbased investigation that focused on divide migration. They concluded that the main divides of Sado have presumably continued to slowly migrate toward the area of faster uplift.…”
Section: Worldwide Tectonic Geomorphological Research Using High-reso...mentioning
confidence: 99%